The synthesis of C2 symmetry diesters of (3R,4R)-TTFOL through a green and stereoselective (2R,3R)-TADDOL rearrangement - Costantino, Andrea Rosana (2015)
An efficient, green, and atom economic methodology for the stereoselective synthesis of C2 symmetry (3R,4R)-TTFOL diester derivatives has been developed. The procedure occurs through a (2R,3R)-TADDOL dioxolane cleavage and rearrangement under mild conditions by its reaction with a carboxylic acid in the presence of TFAA/H3PO4 without the need for an inert atmosphere to give generally high yields.